Impact of Proteins on Aggregation Kinetics and Adsorption Ability of Hematite Nanoparticles in Aqueous Dispersions - Sheng, Anxu; Feng Liu; Xie, Nan; Juan* Liu (Environmental science & technology, 2016)
The initial aggregation kinetics of hematite nanoparticles (NPs) that were conjugated with two model globular proteins—cytochrome c from bovine heart (Cyt) and bovine serum albumin (BSA)—were investigated over a range of monovalent (NaCl) and divalent (CaCl2) electrolyte concentrations at pH 5.7 and 9. The aggregation behavior of Cyt-NP conjugates was similar to that of bare hematite NPs, but the additional electrosteric repulsion increased the critical coagulation concentration (CCC) values from 69 mM to 113 mM in NaCl at pH 5.7. An unsaturated layer of BSA, a protein larger than Cyt, on hematite NPs resulted in fast aggregation at low salt concentrations and pH 5.7, due to the strong attractive patch-charge interaction. However, the BSA-NP conjugates could be stabilized simply by elevating salt concentrations, owing to the screening of the attractive patch-charge force and the increasing contribution from steric force. This study showed that the aggregation state of protein-conjugated NPs is proved to be completely switchable via ionic strength, pH, protein size, and protein coverage. Macroscopic Cu(II) sorption experiments further established that reducing aggregation of hematite NPs via tailoring ionic strength and protein conjugation could promote the metal uptake by hematite NPs under harsh conditions.